2019
DOI: 10.1016/j.bej.2019.107248
|View full text |Cite
|
Sign up to set email alerts
|

Solid state fermentation pilot-scaled plug flow bioreactor, using partial least square regression to predict the residence time in a semicontinuous process

Abstract: Semicontinuous production of fungal compounds was obtained with a Plug Flow Bioreactor (PFB) prototype. • Productions of same metabolites obtained over time at lab scale were used to build a Partial Least Square (PLS) model. • A residence time of solid particles was associated to each PFB compartment using the PLS model. • The PFB prototype was suitable to continuously produce fungal secondary metabolites.• PLS was an innovative approach to evaluate the scale-up of the metabolite production. A R T I C L E I N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Indeed, the cultures have been performed in flasks at laboratory scale and it is notorious in SSF; an increase of production scale leads to the formation of important thermic and water gradients in the medium bed that can negatively affect the production [41]. However, encouraging results have been obtained at pilot scale for NγP production [42].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the cultures have been performed in flasks at laboratory scale and it is notorious in SSF; an increase of production scale leads to the formation of important thermic and water gradients in the medium bed that can negatively affect the production [41]. However, encouraging results have been obtained at pilot scale for NγP production [42].…”
Section: Resultsmentioning
confidence: 99%
“…The cultures were incubated at 29 • C ± 1 • C for 5 days. Flasks were not hermetically closed to allow some oxygen flow by diffusion [4][5][6][7].…”
Section: Solid-state Fermentationmentioning
confidence: 99%
“…One possible valorization of agro-industrial wastes is solid-state fermentation (SSF). SSF is a biotechnological process where microorganisms are cultured in a solid medium in the absence (or near absence) of free water, although some moisture is present to support the microorganism growth and metabolism [4,5]. Many countries in Africa and Europe have published supporting evidence of the use of SSF in agricultural waste valorization, particularly to induce fungal development that can lead to the formation of secondary metabolites, spore production, and the production of enzymes of industrial interest like cellulases, chitinases, amylases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is often necessary to find a compromise between mass and energy transfers qualities and mycelial damages due to agitation. Some studies have reported good productions of spores and enzymes with filamentous fungi belonging to the genera Aspergillus and Trichoderma in agitated SSF systems with lower rotational speedsranging from 1 to 6 rpmand/or intermittent mixings (Carboué et al, 2019;Finkler et al, 2017;Lopez-Ramirez et al, 2018).…”
Section: Scale Up Of Ssf Process For the Production Of Biosurfactantsmentioning
confidence: 99%